AN ELECTROPHORETIC STUDY ON SERUM PROTEINS IN ARABIAN RACE HORSES NATURALLY INFECTED WITH Babesia equi - SULTAN, A.SH. (The Iraqi Journal of Veterinary Medicine, 2022)
Electrophoretic patterns of serum protein in 12 Arabian race horses acutely infected with Babesia equi revealed a significant decrease in albumin (P<0.01) and beta globulins (P<0.05) where, alpha globulins fractions significantly (P<0.01) increased. No significant (P>0.05) changes were recorded in gamma globulins fractions and total serum protein.